An Experimental Study: Aloe vera Extract Mouthwash against Dental Plaque - Amakhul Husna; Rita Herlina; Dian Femala; Hima Mahda Nadia; Hilda Azkiya (JURNAL INFO KESEHATAN, 2025)
Recent studies have demonstrated the potential of Aloe vera as a natural agent in dental care based on in vivo and in vitro evidence; however, research evaluating its effectiveness as a mouthwash remains limited. This study aimed to assess the efficacy of Aloe vera mouthwash in reducing dental plaque among school-aged children in Indonesia. A structured experimental study with a pretest–posttest design was conducted involving 45 children aged 10–12 years in West Kalimantan. Dental plaque levels were measured using the Personal Hygiene Performance (PHP) Index before and after the intervention. The results showed that the mean dental plaque score decreased from 2.76 at baseline to 1.75 after the use of Aloe vera mouthwash. Statistical analysis using a paired t-test indicated a significant reduction in dental plaque scores following the intervention. In conclusion, Aloe vera mouthwash is effective in reducing dental plaque among children and may serve as a potential alternative preventive agent for periodontal disease.